Importance of Metabolic Adaptations in Francisella Pathogenesis - Ziveri, Jason; Barel, Monique; Charbit, Alain (Frontiers in Cellular and Infection Microbiology, 2017)
Francisella tularensis is a highly infectious Gram-negative bacterium and the causative agent of the zoonotic disease tularemia. This bacterial pathogen can infect a broad variety of animal species and can be transmitted to humans in numerous ways with various clinical outcomes. Although, Francisella possesses the capacity to infect numerous mammalian cell types, the macrophage constitutes the main intracellular niche, used for in vivo bacterial dissemination. To survive and multiply within infected macrophages, Francisella must imperatively escape from the phagosomal compartment. In the cytosol, the bacterium needs to control the host innate immune response and adapt its metabolism to this nutrient-restricted niche. Our laboratory has shown that intracellular Francisella mainly relied on host amino acid as major gluconeogenic substrates and provided evidence that the host metabolism was also modified upon Francisella infection. We will review here our current understanding of how Francisella copes with the available nutrient sources provided by the host cell during the course of infection.